Fluorogenic, catalytic, photochemical reaction for amplified detection of nucleic acids - Dutta, Subrata; Fülöp, Annabelle; Mokhir, Andriy (Bioconjugate Chemistry, 2013)
Photochemical, nucleic acid-induced reactions, which are controlled by nontoxic red light, are well-suited for detection of nucleic acids in live cells, since they do not require any additives and can be spatially and temporally regulated. We have recently described the first reaction of this type, in which a phenylselenyl derivative of thymidine (5′-PhSeT-ODNa) is cleaved in the presence of singlet oxygen (Fülöp, A., Peng, X., Greenberg, M. M., Mokhir, A. (2010) A nucleic acid directed, red light-induced chemical reaction. Chem. Commun. 46, 5659-5661). The latter reagent is produced upon exposure of a photosensitizer 3′-PS-ODNb (PS = Indium(III)- pyropheophorbide-a-chloride: InPPa) to >630 nm light. In 2012 we reported on a fluorogenic version of this reaction (Dutta, S., Flottmann, B., Heilemann, M., Mokhir, A. (2012) Hybridization and reaction-based, fluorogenic nucleic acid probes. Chem. Commun. 47, 9664-9666), which is potentially applicable for the detection of nucleic acids in cells. Unfortunately, its yield does not exceed 25% and no catalytic turnover could be observed in the presence of substrate excess. This problem occurs due to the efficient, competing oxidation of the substrate containing an electron rich carbon-carbon double bonds (SCH=CHS) in the presence of singlet oxygen with formation of a noncleavable product (SCH=CHSO). Herein we describe a related, but substantially improved photochemical, catalytic transformation of a fluorogenic, organic substrate, which consists of 9,10-dialkoxyanthracene linked to fluorescein, with formation of a bright fluorescent dye. In highly dilute solution this reaction occurs only in the presence of a nucleic acid template. We developed three types of such a reaction and demonstrated that they are high yielding and generate over 7.7 catalytic turnovers, are sensitive to single mismatches in nucleic acid targets, and can be applied for determination of both the amount of nucleic acids and potentially their localization. © 2013 American Chemical Society.